2018
DOI: 10.1016/j.anihpc.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Minimisers of the Allen–Cahn equation and the asymptotic Plateau problem on hyperbolic groups

Abstract: We investigate the existence of non-constant uniformly-bounded minimal solutions of the Allen-Cahn equation on a Gromov-hyperbolic group. We show that whenever the Laplace term in the Allen-Cahn equation is small enough, there exist minimal solutions satisfying a large class of prescribed asymptotic behaviours. For a phase field model on a hyperbolic group, such solutions describe phase transitions that asymptotically converge towards prescribed phases, given by asymptotic directions. In the spirit of de Giorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 29 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…One step in the proofs that can be applied also to a graph like Γ is the following proposition, which states that shadows are "almost round". The proof is analogous to [25,Proposition 2.3].…”
Section: Shadows and Conesmentioning
confidence: 95%
See 4 more Smart Citations
“…One step in the proofs that can be applied also to a graph like Γ is the following proposition, which states that shadows are "almost round". The proof is analogous to [25,Proposition 2.3].…”
Section: Shadows and Conesmentioning
confidence: 95%
“…A similar variational approach to the one used in this paper was developed by the author in [25] for solving the Allen-Cahn equation on a Cayley graph of a hyperbolic group. There, the equivalent statement to the existence theorem above is proved when (AC) has the form ρ∆g(x) − V ′ (xg) = 0 with asymptotically small ρ (see [25,Theorem 4.14]). In Theorem 3.7 of that paper it has been shown that for small enough ρ, all global minimisers converge to either c0 or c1, which gives additional motivation for studying the Dirichlet problem in the form presented in theorem A above.…”
Section: Variational Approach and Minimal Boundariesmentioning
confidence: 99%
See 3 more Smart Citations